A Branch-and-Reduce Approach for Solving Generalized Linear Multiplicative Programming. (5th July 2011) - Wang, Chun-Feng; Liu, San-Yang; Zheng, Geng-Zhong
Abstract : We consider a branch-and-reduce approach for solving generalized linear multiplicative programming. First, a new lower approximate linearization method is proposed; then, by using this linearization method, the initial nonconvex problem is reduced to a sequence of linear programming problems. Some techniques at improving the overall performance of this algorithm are presented. The proposed algorithm is proved to be convergent, and some experiments are provided to show the feasibility and efficiency of this algorithm.